Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Project Based Learning untuk Meningkatkan Kemampuan Menulis Narasi Konteks Ekoliterasi pada Pelajaran Bahasa Indonesia Kelas IV Sekolah Dasar - Likran Isnadi; Abdul Muktadir; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar, 2024)
This research aims to develop: Student Worksheets (LKPD) based on project based learning to improve the ability to write narratives in an ecoliteracy context. The research was conducted at SDN 85 Central Bengkulu in class IV. This research is development research (Research and Development) with a 4D model, namely the definition, design, development and disseminate stages. The instruments used were feasibility test questionnaires and student response questionnaires and teacher interview guidelines. The feasibility test was carried out by 6 validators. User response testing was carried out on 20 class IV students and 1 class teacher in the trial class. Data analysis was used to determine the validity of the LKPD using cross tabulation and distribution of questionnaires for student responses as well as interviews for teacher responses in using percentage technique LKPD and processed descriptively. The results of the LKPD feasibility test by the validator were reviewed from the material, language and display presentation aspects, the material feasibility was obtained 0.80 (feasible criteria), the language feasibility results were 0.70 (feasible criteria) and the appearance feasibility results were 0.80 (very feasible criteria). The results of the LKPD field test by conducting a post test and pre test with the results of the knowledge gain test showed 20 students with a high criterion gain count of 4 students with a percentage of 20% then medium criteria 14 students with a percentage of 70% then low criteria 2 students with a percentage 10 %. Then, to test the gain of narrative text writing skills, 15 people had high criteria or 75% and 5 people had medium criteria or 25%. Apart from that, the results of interviews with class IV teachers showed a positive response. In other words, the LKPD used is beneficial and effective for use as a learning medium in improving students' narrative text writing skills.